Method for acquiring accurate coordinates of the source point in electron backscatter diffraction. (23rd August 2021) - Zhang, Yongsheng; Shen, Yitian; Peng, Fan; Jiang, Caifen; Li, Wei; Miao, Hong; Huang, Fuqiang; Zeng, Yi
Abstract: An electron backscatter diffraction device is an important accessory for a scanning electron microscope and can provide crystal structure orientation and phase content data through analysis of electron backscatter diffraction patterns. The acquisition of these data depends on pattern indexing, including interplanar angle calculation and crystal plane indexation. The coordinates of the source point are key points for interplanar angle calculation, and they vary with the movement of the incident beam. In this study, we first combined the grey gradient calculation with screen moving method to achieve accurate positioning of source point and obtained coordinates of source point with sub‐pixel precision. The errors of three coordinates were 0.07%, 0.06% and 0.04%, respectively. By using this coordinate of source point to conduct interplanar angle calculation the maximum error was 0.53°, which was a good proof of the accuracy of source point positioning. Then we established the relationship between source point coordinates variation and incident beam movement. Coordinates can be given out based on the displacement of beam directly. And to illustrate the accuracy, interplanar angle calculation was performed and the maximum error was 0.81°. This means that the relationship between variation of source point coordinates and beam movement is highly accurate.